Kuasa Elit Lokal dan Kapitalis Pasca Otoritarianisme: Perspektif Pribumi dan Etnis Tionghoa - Fajar (JPP (Jurnal Politik Profetik), 2023)
The study of capitalism in Indonesia cannot be separated from the two capitalist groups, namely the Indigenous and ethnic Chinese who dominate the economy in Indonesia. This article describes the power of local elites and post-authoritarian capitalist capitalists by looking at how Indigenous and Chinese ethnic groups reproduce political roles and their involvement in the national economy. The main objective is to find out how the position of local elite power and capitalists in Indonesian political practice. The method used in this study uses a phenomenological approach developed by Husserl and Heidegger which looks at individual experiences and individual existence. In general, this study concludes that the indigenous and ethnic Chinese elites are the differentiator where the ownership of capitalization by ethnic Chinese is part of the history of capitalism in Indonesia which then reaches all provinces in Indonesia through economic transformation in which material ownership becomes so strong domestic investment in Indonesia is different from the indigenous groups themselves, which are unequal because in general the natives cannot develop a national scale economic pattern.